Performance of fixed-bed KOH impregnated activated carbon adsorber for NO and NO2 removal in the presence of oxygen - Lee, YW; Choi, DK; Park, JW (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
KOH-impregnated activated carbon (K-IAC) was used in this study. This paper contains observation the adsorption behavior of NO and NO2 with/without oxygen and with different bed depths of adsorbent. The paper also defines surface chemical changes due to NOx adsorption. By using a simple design of adsorber. the packed amount of adsorbent for NOx abatement for 6 months on a pilot scale was calculated. When oxygen was present, NO and NO2 had a great improvement in adsorptivity. Adsorption of NO2 forms a oxide crystal on the surface of the K-IAC and at the same time produces NO. which acts to bring about increased adsorptivity. The higher the bed of adsorbent was, the more NO was produced and the longer the breakthrough time took. The adsorber was designed in a scale-up condition where NO, NO2 and O-2 were applied to K-IAC. The adsorbate that consumed the least packed amount was NO2-air followed by NO2-N-2, NO-air and NO-N-2. The results of the experiment demonstrated that with regard to adsorption of NO and NO2 on K-IAC, the presence of oxygen and the bed depth of adsorbent were the biggest variables to adsorptivity. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: ADSORPTION; REDUCTION; CATALYSTS; GAS; PORE; COAL